2020
DOI: 10.1038/s41598-020-63600-9
|View full text |Cite
|
Sign up to set email alerts
|

An outcome-wide analysis of bidirectional associations between changes in meaningfulness of life and health, emotional, behavioural, and social factors

Abstract: Daisy fancourt the sense that one is living a meaningful life is associated with positive health outcomes, but less is known about the role of changes in sense of meaning. this outcome-wide analysis investigated bidirectional associations between changes in ratings of doing worthwhile things in life and 32 factors in 6 domains of human function in 5,694 men and women (M = 66.65 years) from the English Longitudinal Study of Ageing. participants rated the extent they felt that the things they did in life were wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 50 publications
4
28
0
Order By: Relevance
“…An outcome-wide approach was applied, in which multiple outcomes were considered for a single exposure (VanderWeele 2017a). This approach has been theoretically argued (VanderWeele 2017a;VanderWeele et al 2020b, a) and empirically confirmed as effective in presenting temporal associations across the whole spectrum of outcomes (Białowolski et al 2019;Chen et al 2019;Chen and Vanderweele 2018;Kim et al 2020;Pawlikowski et al 2019;Steptoe and Fancourt 2020;Węziak-Białowolska et al 2018). It has the advantage of avoiding cherry-picking of significant results only, limits the risk of p-hacking (Head et al 2015;Lakens 2015) and seems to facilitate reporting of the so-called 'negative' or 'non-significant' findings, which has been already proven problematic in scientific publishing due to resistance of journal editors to publish negative results (Fanelli 2010(Fanelli , 2012Ioannidis 2005;Matosin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An outcome-wide approach was applied, in which multiple outcomes were considered for a single exposure (VanderWeele 2017a). This approach has been theoretically argued (VanderWeele 2017a;VanderWeele et al 2020b, a) and empirically confirmed as effective in presenting temporal associations across the whole spectrum of outcomes (Białowolski et al 2019;Chen et al 2019;Chen and Vanderweele 2018;Kim et al 2020;Pawlikowski et al 2019;Steptoe and Fancourt 2020;Węziak-Białowolska et al 2018). It has the advantage of avoiding cherry-picking of significant results only, limits the risk of p-hacking (Head et al 2015;Lakens 2015) and seems to facilitate reporting of the so-called 'negative' or 'non-significant' findings, which has been already proven problematic in scientific publishing due to resistance of journal editors to publish negative results (Fanelli 2010(Fanelli , 2012Ioannidis 2005;Matosin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that prosociality increases perceptions of meaning has been found in several empirical studies. Aspects of prosociality such as being a ‘giver’ and volunteering are correlated with having a stronger sense of meaning [ 26 28 ], and volunteering is also associated with increases in meaning over time [ 29 ]. Prosociality and meaning are also related at the daily level [ 30 32 ], with evidence showing that performing prosocial acts in everyday life is associated with experiencing greater meaning on those days [ 33 , 34 ].…”
Section: Prosociality As a Powerful Source Of Meaningmentioning
confidence: 99%
“…Study about meaningfulness of life and health, emotional, behavioral, and social factors in England showed similar result, where employment status was not affecting one's sense of living a meaningful life which later lead to better health status. But the results become significant if it is related to individual wealth instead of being either employed or unemployed (Steptoe and Fancourt, 2020).…”
Section: Discussionmentioning
confidence: 95%